2016
DOI: 10.5812/jjm.33498
|View full text |Cite
|
Sign up to set email alerts
|

Study of Genetic Variation of Leishmania major Based on Internal Transcribed Spacer 1 (ITS1) in Chabahar, Iran

Abstract: BackgroundZoonotic cutaneous leishmaniasis (ZCL) is polymorphic disease that may show various clinical manifestations.ObjectivesThis study investigates the determination of genetic variation within the species of Leishmania major isolates from new cases in Chabahar, a port city in Southeast Iran (situated at the Iran-Pakistan border). Migration in this region indicates that leishmaniasis is spreading gradually, and a new micro-habitat focus appears each year.Materials and MethodsA variety of nucleic acid detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These findings are similar to studies reported that L. tropica isolates included the highest divergence in ITS1 genes ( 26 ). Similar to a study on L. major with 98.2% similarity, results of the current study showed a limited genetic variation with seven haplotypes seen in L. major (H1–H7) ( 25 ). Four haplotypes of L. major were found in a distinct clade in nine rodent isolates in Central Iran ( 23 ) and six haplotypes of L. major were identified through PCR-RFLP of rodent samples using ITS1 markers ( 8 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are similar to studies reported that L. tropica isolates included the highest divergence in ITS1 genes ( 26 ). Similar to a study on L. major with 98.2% similarity, results of the current study showed a limited genetic variation with seven haplotypes seen in L. major (H1–H7) ( 25 ). Four haplotypes of L. major were found in a distinct clade in nine rodent isolates in Central Iran ( 23 ) and six haplotypes of L. major were identified through PCR-RFLP of rodent samples using ITS1 markers ( 8 ).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have amplified ITS-1 region of the ribosomal DNA repeat unit (rDNA-ITS1) for the recognition of Iranian Leishmania spp. ( 8 , 23 25 ). In the present study, a number of unknown Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…This region is highly conserved among species (178). The ITS region as a target for differentiation of Leishmania at species and strain level has been used in different studies (102,105,132). As a whole, it should be noted that apply of two genetic markers simultaneously could provide more data regarding genetic map of the Leishmania parasite particularly in an endemic focus.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products were visualized using ultraviolet transillumination with GelRed TM dye (GIBCO BRL Life Technologies, Inc., Gaithersburg, MD, USA) on 1.55 agarose gel (SIGMA, St. Louis) in 1X TAE buffer for 45 min at 100 V after electrophoresis; the size of the amplified product was determined by comparison with a 100 bp ladder (Sigma-Aldrich, USA). [2] The results were positive for Leishmania infantum [Figure 2].…”
Section: Investigationsmentioning
confidence: 99%